Tissue distribution and functional analyses of the constitutively active orphan G protein coupled receptors, GPR26 and GPR78 - Jones, Philip G.; Nawoschik, Stanley P.; Sreekumar, Kodangattil; Uveges, Albert J.; Tseng, Eugene; Zhang, Lynn; Johnson, Jeremy; He, Lan; Paulsen, Janet E.; Bates, Brian; Pausch, Mark H. (Biochimica et biophysica acta, 2007)
GPR26 and GPR78 are orphan GPCRs (oGPCRs) that share 51% amino acid sequence identity and are widely expressed in selected tissues of the human brain as well as the developing and adult mouse brain. Investigation of the functional activity of GPR26 and GPR78 via expression in HEK293 cells showed that both proteins are constitutively active and coupled to elevated cAMP production. Accordingly, in yeast, GPR26 demonstrated apparent agonist-independent coupling to a chimeric Gpa1 protein in which the 5 C-terminal amino acids were from Gαs. A comparison of the proteins revealed an atypical glutamine residue in GPR78 in place of the conserved arginine residue (R3.50) in the so-called DRY box. Site-directed mutants R3.50 in GPR26 were constructed and retained their constitutive activity suggesting that these 2 receptors activate G proteins in a manner that is distinct from other group 1 GPCRs.